Comparative morphometric analysis of the gastrointestinal tract of the captive greater cane rat (Thryonomys swinderianus) and African giant pouched rat (Cricetomys gambianus) - Byanet, Obadiah; Abayomi, Akileye O.; Aondohemba, Tyagher J. (Italian Journal of Anatomy and Embryology, 2015)
Comparative morphometric analysis of the gastrointestinal tract of the captive greater cane rat (Thryonomys swinderianus) and African giant pouched rat (Cricetomys gambianus) Obadiah Byanet, Akileye O. Abayomi, Tyagher J. Aondohemba Department of Veterinary Anatomy, College of Veterinary Medicine, University of Agriculture, Makurdi, Benue State, Nigeria Submitted September 5, 2014; accepted revised December 22, 2014 Abstract The greater cane rats (Thryonomys swinderianus) and African giant pouched rats (Cricetomys gambianus) are among the largest rodents in Africa, undergoing domestications for meat and research purposes. The aim of this study was to explore whether there are any quantitative anatomical gastrointestinal adaptations associated with their omnivorous or herbivorous diets. In the African giant rat, the mean gastrointestinal tract length and colon width of the males were significantly higher than their females counterpart (P < 0.05 and P < 0.01, respectively). In a similar way, the mean gastrointestinal tract weight, stomach length and jejunal width in males greater cane rat were significantly higher than in the females (P < 0.05, P < 0.01 and P < 0.01 respectively). The monogastric, omnivores African giant pouched rats had mean significant stomach length and width than greater cane rat (P < 0.01 and P < 0.01 respectively). Also, the duodenal length, jejunal and ileal widths were higher in the former than in the latter (P < 0.05, P < 0.05 and P < 0.01 respectively). The monogastric, herbivore greater cane rats had higher mean cecal width and colon length than the African giant pouched rat (P < 0.01 and P < 0.01 respectively). In conclusion, the African giant pouched rat had larger stomach and longer and wider small intestine, compared to the greater cane rat, which instead had more prominent cecum and wider and longer colon. This suggests that greater cane rats are hindgut fermenting herbivores (cecal fermenter), as is the case in most rodent species. Key words Stomach, small intestine, large intestine, morphometry, captivity, light microscopy.